Orthopedic Research in Nepal: Status, Challenges, and Opportunities! - Banskota, Bibek (Nepal Orthopaedic Association Journal, 2025)
Nepal faces significant challenges in developing a robust orthopedic research infrastructure despite a growing burden of musculoskeletal conditions affecting its population. This editorial examines the current state of orthopedic research in Nepal, highlighting persistent gaps in evidence-based studies and suggesting potential pathways for improvement.